1998
DOI: 10.1093/hmg/7.11.1713
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse Y Chromosome Interval Necessary for Spermatogonial Proliferation is Gene Dense with Syntenic Homology to the Human AZFa Region

Abstract: The Delta Sxrb deletion interval of the mouse Y chromosome contains Spy, a spermatogenesis factor gene(s) whose expression is essential for the postnatal development of the mitotic germ cells, spermatogonia. The boundaries of Delta Sxrb are defined by the duplicated genes Zfy1 and Zfy2 and four further genes have previously been mapped within the interval: Ube1y and Smcy, linked with Zfy1 on a contig of 250 kb, and Dffry and Uty, which were unanchored. The interval was estimated to be >450 kb. In order to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 58 publications
2
61
0
Order By: Relevance
“…Comparative mapping studies have shown that most eutherian orders share a core set of conserved, X-degenerate, Y-borne genes [6,7,[10][11][12][13][14][15][16]. Previous studies mapped eight of these to the feline Y chromosome [13], but efforts to isolate additional feline Y-borne loci were largely unsuccessful, primarily due to mammalian conserved X-Y primers preferentially amplifying only X-specific homologs in male cat DNA.…”
Section: Isolation and Mapping Of New Feline X-degenerate Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative mapping studies have shown that most eutherian orders share a core set of conserved, X-degenerate, Y-borne genes [6,7,[10][11][12][13][14][15][16]. Previous studies mapped eight of these to the feline Y chromosome [13], but efforts to isolate additional feline Y-borne loci were largely unsuccessful, primarily due to mammalian conserved X-Y primers preferentially amplifying only X-specific homologs in male cat DNA.…”
Section: Isolation and Mapping Of New Feline X-degenerate Genesmentioning
confidence: 99%
“…To date, however, all published comparative studies have focused on which human (or mouse) Y chromosome genes are present or not in other mammalian species [6][7][8][9][10][11][12][13][14][15]. While these studies, particularly those in marsupials and monotremes [16][17][18][19][20], have been extremely useful in highlighting broader evolutionary patterns, there still exists a fundamental gap in our understanding of the novel gene content and processes by which Y chromosome genes have been acquired or lost in other major lineages of mammals.…”
Section: Introductionmentioning
confidence: 99%
“…DBY has an X-homologue, DBX, located on Xp11, which escapes X-inactivation and has 91.7% sequence identity at the protein level in humans. Slightly different from the human DBY gene, mouse Dby has a structural homolog called Ddx3x on the X chromosome and an autosomal homolog, D1Pas1, on mouse chromosome 1 [8,9]. Furthermore, the spermatogenesis-specific function of Dby is not obvious in mice when compared with humans [10].…”
mentioning
confidence: 94%
“…In contrast to humans mouse Ddx3y protein is found to be dispensable for spermatogenesis (24), but Ddx3y mRNA is retained in mouse spermatozoa and appears to contribute to early zygotic development (25). The mouse Ddx3y gene also has an X-chromosomal homologue Ddx3x (26). It is supposed that molecular functions of Ddx3y protein may be carried out by Ddx3x representing the same expression pattern in mouse testes (23).…”
Section: Discussionmentioning
confidence: 99%